Dune part two - Zimmer, Hans 1957-; Herbert, Frank 1920-1986 (Universal Pictures Germany GmbH, 2024)
Paul Atreides, alongside Chani and the Fremen, seeks vengeance against the conspirators who destroyed his family, while grappling with the dilemma of choosing between his love for Chani and the fate of the universe. Amidst the turmoil caused by the destruction of House Atreides by House Harkonnen, Paul and his mother Lady Jessica integrate into Fremen society on Arrakis, where they confront suspicion and skepticism while fulfilling prophecies and facing the challenges of the desert planet. As Paul embraces Fremen customs and earns their respect, his bond with Chani deepens, all while the political intrigue involving the Harkonnens and the Bene Gesserit unfolds around them
Bildformat 16:9 (2,39:1)
Über eine Stunde Bonusmaterial: das Set-Design der Fremenwelt, Chakobsa-Unterricht, Wurmreiten, Dune: die Sounds der Wüste
Orig.: USA, 2024
Keywords: Dune (Imaginary place) / Drama; Interplanetary voyages / Drama; Political corruption / Drama; Prophecies / Drama; Video recordings for the hearing impaired; Vidéos pour personnes handicapées auditives; Action films; Adventure films; Science fiction films; Fantastic films; Film adaptations; Actionfilm; Abenteuerfilm; Fantastischer Film; Verfilmung; Science-Fiction-Film; Film; Blu-Ray-Disc